Preliminary results for the detection method of perfluoroalkyl substances (PFASs) residues in pork (International Journal of Health, Animal Science and Food Safety, 2017)
The perfluoroalkyl substances (PFASs) residues, which come from environmental pollution, tend to accumulate in the food chain (EFSA, 2008; Guerranti et al., 2013). 17 chemicals of PFASs family were selected for this study. Fresh pork samples were extracted by Waters® WAX SPE (solid phase extraction) cartridges. All extracted samples were analyzed by liquid chromatography tandem mass spectrometry (LC-MS/MS). The results of calibration curves of each PFAS were good, the R2 values ranging from 0.9901 to 0.9993. The Recoveries were in the range 80%-119%. The protocol of extraction by Waters® WAX SPE cartridge will be applied in future studies.
Keywords: Perfluoroalkyl substances (PFASs); Residue; Liquid chromatography tandem mass spectrometry; Pork; WAX cartridge.